Respuesta :

Answer:

i think 2nd one is true....f(-2)=g(-2)

Answer:

A is correct: [tex]f(0)=g(0)[/tex]

Step-by-step explanation:

To find this answer, we first must identify what [tex]f(x)[/tex] and [tex]g(x)[/tex] means.

[tex]f(x)[/tex] shows the y value of the line at the specified x value.

[tex]g(x)[/tex] shows the y value of the line at the specified x value.

So in order to solve this problem, we must look at each of the options and see which one is true.

If we take a look at the first option...

[tex]f(0)=-2[/tex] in this example and [tex]g(0)=-2[/tex] as well.

[tex]-2=-2[/tex] and therefore, option A is correct.